Legal Protection Against Tobacco Smoke Harmful Effects on Children - David Anggara Putra; Mulyanto (Journal of Law, Politic and Humanities, 2024)
Tobacco smoking is harmful either for smokers or second-hand smokers. Indonesia is the country with the third highest number of smokers in the world and the largest number of smokers in Southeast Asia. Active smokers in Indonesia estimated to reach 70 million people. Of that number, 7.4% are children aged 10-18 years. The aims of this research are to examine the legal protection of children from the dangers of tobacco smoke and also examine the role of the government in protecting children from the dangers of tobacco smoke. The research method used is normative research. Normative legal research is conducted using a variety of primary legal materials, which are in the form of statutory regulations, as well as secondary legal materials. In Indonesia, a number of legal regulations focus on protecting children from the negative effects of smoking, both directly and indirectly. Some of these regulations include: Law number 35 of 2014 concerning Child Protection, Law number 17 of 2023 concerning Health, Government Regulation number 109 of 2012 concerning Safeguarding of Materials Containing Addictive Substances in the Form of Tobacco Products for Health, Regional Regulations on Non-Smoking Areas (KTR)